2021
DOI: 10.1152/ajpgi.00129.2021
|View full text |Cite
|
Sign up to set email alerts
|

PPARα agonist fenofibrate attenuates iron-induced liver injury in mice by modulating the Sirt3 and β-catenin signaling

Abstract: Iron accumulation is frequently associated with chronic liver diseases. However, our knowledge on how iron contributes to the liver injury is limited. Aberrant Wnt/β-catenin signaling is a hallmark of several hepatic pathologies. We recently reported that peroxisome proliferator activated receptor alpha (PPARα) agonist, fenofibrate prevents iron induced oxidative stress and β-catenin signaling by chelating the iron. Sirtuin3 (Sirt3), a type of NAD+-dependent deacetylase that plays a critical role in metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
8
1
Order By: Relevance
“…In contrast to our results, a study in Pparα knockout mice treated with 100 mg/kg FN for 6 weeks showed downregulation of hepatic Sirt3 expression, indicating the dependence of Sirt3 expression on PPARα in mouse liver (Mandala et al, 2021). Moreover, the FN treatment prevented iron-induced downregulation of hepatic Sirt3 in wild-type iron-overloaded mice (Mandala et al, 2021). Modulation of SIRT3 expression by FN appears to be variable under different experimental conditions.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, a study in Pparα knockout mice treated with 100 mg/kg FN for 6 weeks showed downregulation of hepatic Sirt3 expression, indicating the dependence of Sirt3 expression on PPARα in mouse liver (Mandala et al, 2021). Moreover, the FN treatment prevented iron-induced downregulation of hepatic Sirt3 in wild-type iron-overloaded mice (Mandala et al, 2021). Modulation of SIRT3 expression by FN appears to be variable under different experimental conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…Reports on hepatic Sirt3 expression upon FN treatment showed either no impact of the drug (approx. 400 mg/kg/day, 5 days) (Li & Wu, 2018) or prevention of iron overload-induced downregulation of Sirt3 (100 mg/kg, i.p., 6 weeks) (Mandala et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies confirmed that a decrease in NAD levels could affect the activities of NAD-dependent enzymes, such as the SIRT family proteins, and then promote the TGF-β signaling pathway [ 16 , 41 ]. Activating NAD-dependent enzymes or replenishing NAD by NAD precursors could attenuate TGF-β-related diseases [ 41 , 42 , 43 , 44 ]. In our study, we observed that TGF-β significantly promoted the migration and invasion of HepG2 cells in vitro, whereas NR supplementation was found to inhibit such effects.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, iron overload can inhibit Sirt3 activity, leading to mitochondrial ROS accumulation and autophagy, which causes bone marrow damage (Zhou et al, 2021). Sirt3 activation plays a protective role in iron-overloaded liver cells via the Wnt/β-catenin pathway (Mandala et al, 2021). These findings shows that Sirt3 can control cell death mediated by iron overload.…”
Section: Sirtuin 3 and Ferroptosismentioning
confidence: 98%